Effect of scion varieties and wrapping materials on success of tongue grafting in Kiwifruit (Actinidia deliciosa) in Dolakha, Nepal - Pandey, Divya; Shrestha, Bishal; Sapkota, Madan; Banjade, Sarita (Journal of Agriculture and Natural Resources, 2019)
This study was conducted at Boch, Bhimeshwor-8, Dolakha, Nepal from January to May, 2019 to study the effect of scion variety and wrapping materials on growth performance of kiwi seedling rootstock. The field experiment was carried out in Factorial Randomized Complete Block Design using four replications. The treatments consisted of four scion varieties (Monty, Bruno, Hayward, Allison) grafted onto one year old kiwi seedling (Actinidia deliciosa) and two types of wrapping material (Grafting tape and Polyethylene plastic). The measured traits included sprout length, diameter, number of leaves, and number of sprouted bud per graft, graft success, mortality and survival percentage of grafts. The success rate of kiwi grafting was significantly affected by the scion variety and the wrapping materials. Allison variety showed the minimum days (61.72 days) to first sprouting and the maximum length of sprouts, diameter, number of leaves and number of sprouted bud per graft at the final observation. Monty variety showed the lowest growth performance. The maximum graft success (96.87%) and survival percentage of grafts (93.75%) was observed in Allison variety statistically at par with Bruno and Hayward and the lowest graft success(73.44%) and survivability(64.21%) was observed in Monty due to high mortality of the sprouted grafts. Grafting tape was superior to polyethylene plastic in terms of days to first sprouting (64.08 days), number of sprouted buds per grafts, number of leaves, graft success (92.18%) and survival of the grafts (87.01%) at the final observation. Interactive effect was found non-significant. In a nutshell, Allison is the best scion variety for grafting under the climatic condition of Dolakha and the grafting tape was the suitable tying material.